REALIZING SUSTAINABLE ISLAMIC EDUCATION THROUGH AN INCLUSIVE INTEGRATIVE PROGRAM AT SD NEGERI 2 KARANGNANGKA BUKATEJA PURBALINGGA - Marfiyah Marfiyah; Muhamad Slamet Yahya (LP2M IAI Al-Khairat Pamekasan, 2026)
This article aims to examine and formulate strategies for the implementation of sustainable Islamic education through an integrative and inclusive program approach at SD Negeri 2 Karangnangka Bukateja Purbalingga. Islamic education plays a central role in shaping the character of students from an early age, but its implementation is often fragmented and fails to address the reality of diversity in the school environment. An inclusive integrative program is seen as a strategic approach that integrates religious material with social, cultural, and diversity values, as well as accommodating the needs of all students, including those with special needs. The method used in this study is qualitative with a case study approach at schools that have implemented inclusive principles in Islamic Religious Education. Data were collected through observation, in-depth interviews, and documentation. The expected result is the formation of an integrative and inclusive Islamic Religious Education model or framework that is not only academically relevant but also applicable in the context of basic learning. Thus, this article is expected to contribute to the development of a more equitable, sustainable, and diversity-oriented education system.